Q. 1 A3.7( 13 Votes )

If <span lang="EN

Answer :

Formula used.


(a + b)2 = a2 + b2 + 2ab


(a + b)3 = a3 + b3 + 3ab(a + b)


Let a = m and b =


(a + b)2 = a2 + b2 + 2ab


(m + )2 = m2 + 2 + 2 × m ×


(√3)2 = m2 + + 2 × 1


3 = m2 + + 2


m2 + = 3 – 2 = 1


(a + b)3 = a3 + b3 + 3ab(a + b)


(m + )3 = m3 + 3 + 2 × m × × (m + )


(√3)3 = m3 + + 2 × 1 × (√3)


3√3 = m3 + + 2√3


m3 + = 3√3 – 2√3 = √3[3 – 2]


= √ 3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In each of the foWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

If we subtract <sWest Bengal Board - Mathematics

Let us write a raWest Bengal Board - Mathematics

The highest powerWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

Let us rationalizWest Bengal Board - Mathematics

Let us write simpWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics

Let us fill in thWest Bengal Board - Mathematics